Leishmania Mitochondrial Genomes: Maxicircle Structure and Heterogeneity of Minicircles - Camacho, Esther (Genes (Basel), 2019)
The mitochondrial DNA (mtDNA), which is present in almost all eukaryotic organisms, is a useful marker for phylogenetic studies due to its relative high conservation and its inheritance manner. In Leishmania and other trypanosomatids, the mtDNA (also referred to as kinetoplast DNA or kDNA) is composed of thousands of minicircles and a few maxicircles, catenated together into a complex network. Maxicircles are functionally similar to other eukaryotic mtDNAs, whereas minicircles are involved in RNA editing of some maxicircle-encoded transcripts. Next-generation sequencing (NGS) is increasingly used for assembling nuclear genomes and, currently, a large number of genomic sequences are available. However, most of the time, the mitochondrial genome is ignored in the genome assembly processes. The aim of this study was to develop a pipeline to assemble Leishmania minicircles and maxicircle DNA molecules, exploiting the raw data generated in the NGS projects. As a result, the maxicircle molecules and the plethora of minicircle classes for Leishmania major, Leishmania infantum and Leishmania braziliensis have been characterized. We have observed that whereas the heterogeneity of minicircle sequences existing in a single cell hampers their use for Leishmania typing and classification, maxicircles emerge as an extremely robust genetic marker for taxonomic studies within the clade of kinetoplastids.